Microbial release of exopolymeric substances and their role in removal of pollutants from wastewater - Işıl Arslan Topal, E.; Topal, Murat (Elsevier, 2020)
Activated sludge samples were seasonally collected from the aeration tanks of the Municipal Wastewater Treatment Plant located in Elazığ city (Turkey). Mixed liquor suspended solids (MLSS), mixed liquor volatile suspended solids (MLVSS), total solids (TS), suspended solids (SS), volatile solids (VS), chemical oxygen demand (COD), and sludge volume index (SVI) of the activated sludge were seasonally monitored in the treatment plant. Exopolymeric substances (EPS) were extracted in the samples collected. The EPS decreased in summer, while the EPS content was the highest in winter. The TB-EPS part of EPS was higher than the LB-EPS part of the EPS in all seasons. The lowest TB-EPS and LB-EPS were determined in summer, while the highest TB-EPS and LB-EPS were determined in winter. The carbohydrate, protein, and humic substance fractions of TB-EPS and LB-EPS followed the order of protein?>?carbohydrate?>?humic substance in all seasons. There was a negative correlation between the EPS content and SVI. The relationships between EPS and the removal efficiencies of TS, SS, and VS were quite low, while the relationship between COD removal and EPS was quite high. © 2021 Elsevier Inc. All rights reserved.
Keywords: COD; EPS; Volatile solids; Wastewater treatment plant